CYP3A4/5 mediates the metabolic detoxification of humantenmine, a highly toxic alkaloid from Gelsemium elegans Benth. Issue 9 (22nd May 2019) - Sun, Rongjin; Chen, Minghao; Hu, Yanxian; Lan, Yao; Gan, Lili; You, Guoquan; Yue, Min; Wang, Hongmei; Xia, Bijun; Zhao, Jie; Tang, Lan; Cai, Zeng; et al.
Abstract: Gelsemium elegans Benth., a well‐known toxic herbal plant, is widely used to treat rheumatic arthritis, inflammation and other diseases. Gelsemium contains humantenmine (HMT), which is an important bioactive and toxic alkaloid. Cytochrome P450 enzymes (CYPs) play important roles in the elimination and detoxification of exogenous substances. This study aimed to investigate the roles of CYPs in the metabolism and detoxification of HMT. First, metabolic studies were performed in vitro by using human liver microsomes, selective chemical inhibitors and recombinant human CYPs. Results indicated that four metabolites, including hydroxylation and oxidation metabolites, were found in human liver microsomes and identified based on their high‐resolution mass spectrum. The isoform responsible for HMT metabolism was mainly CYP3A4/5. Second, the toxicity of HMT on L02 cells in the presence of the nicotinamide adenine dinucleotide phosphate system (NADPH) was significantly less than that without NADPH system. A CYP3A4/5 activity inhibition model was established by intraperitoneally injecting ketoconazole in mice and used to evaluate the role of CYP3A4/5 in HMT detoxification. In this model, the 14‐day survival rate of the mice decreased to 17% after they were intragastrically treated with HMT, along with hepatic injury and increasing alanine aminotransferase (ALT) /aspartate aminotransferase (AST) levels. Overall, CYP3A4/5 mediated the metabolism and detoxification of HMT. Abstract : Humantenmine (HMT), one of the most toxic alkaloids from Gelsemium, was transformed into four major metabolites in human liver microsomes. The main isoform responsible for HMT metabolism was cytochrome P450 (CYP)3A4/5. When the CYP3A4/5 activity in mice intragastrically treated with HMT was inhibited, their 14‐day survival rate decreased to 17%, along with increasing hepatic alanine aminotransferase/aspartate aminotransferase levels. Overall, CYP3A4/5 mediated the metabolism and detoxification of HMT.